Situation Report of Clinical and Climatic Pattern Changes in Dengue Outbreaks in Bangladesh 2024–2025 - Hossain, Tanvir; Chayan, Famous Uddin; Iqbal, Hrishik; Alam, Fahadul; Syrmos, Nikolaos (Journal of Current Health Sciences, 2025)
Dengue is still a big public health problem in Bangladesh, and the number of cases has risen rapidly in the last several years.  This review integrates epidemiological, clinical, and environmental data to clarify the determinants contributing to the country's dengue crisis.  A systematic literature search from 2001 to 2025 was carried out using PubMed and the Cochrane Library, resulting in 50 pertinent papers regarding dengue epidemiology, transmission dynamics, and health effects in Bangladesh.  The first report of dengue was in 1960, and the first epidemic was in 2000.  Dengue has since become endemic, with huge outbreaks in 2019 (101,354 cases; 164 deaths) and a terrible peak in 2023 (321,179 hospitalizations; 1,705 deaths).  Aedes aegypti has had good reproduction conditions because of changing weather, rising temperatures, unpredictable rainfall, and fast, unplanned urbanization.  Epidemiological changes encompass ongoing year-round transmission, an increase in secondary infections attributable to several serotypes, and a geographical spread from urban Dhaka to semi-urban and rural areas, including the Cox’s Bazar refugee camps.  In clinical practice, patients are increasingly diagnosed with atypical or "expanded dengue syndrome," and mortality is closely linked to shock and subsequent infections.  The expenses to society for each incidence are high, averaging US$479 in urban Dhaka.  People who are more likely to get sick or have mental health problems are youngsters, pregnant women, and the elderly.  Evidence shows that climate change and urbanization are working together to lengthen the dengue season, make epidemics worse, and put a load on Bangladesh's healthcare system.  To lessen the growing threat, it is important to improve surveillance, vector management, and investment in healthcare resilience.